PERGUMULAN SYARI'AT ISLAM DENGAN POLITIK DI ACEH - Hasanuddin Yusuf Adan (Al-Ijtima`i: International Journal of Government and Social Science, 2022)
Actually, Islamic shariah has been united with Acehnese society for a long time from the era of Sultan Iskandar Muda in the seventeenth century until nowadays. The relationship between the government and Acehnese society especially for Islamic shariah has long been agreed and accepted in their daily life. Historically, when Islam was first introduced in this area, the Acehnese society were accepted by the whole society without having any obstacle. They accepted Islam peacefully and there was no coercion as well as refusal. This can be proved when Islam was introduced in Peureulak, there had not been happening chaos and riot within Acehnese society. This circumstance can also be read in the history book related to the coming of Islamic shariah in Aceh. Anyway, it was different from the spread of Islam in Java which was brought and propagated by the Acehnese ulama-Fatahillah. At that time, most of Hindus particularly those who were from the middle and high class community refused Islam and even fought against Islam and a few of them escaped to Bali. Then the questions coming up; why Islamic Shariah and politics in Aceh are in chaos and how to solve this problem. Truely speaking, the dispute between politics and Islamic shariah in Aceh has been happening since Aceh became a part of Indonesia in 1945. Probably this was happening when Indonesia started applying under secular country especially based on the law applied here. Therefore, the dispute between Islamic shariah and secular regulation automatically occured. It is not exaggeration to say that Islamic shariah cannot be appropriated with the concept of secular state. Next solution is to change the concept of Indonesian secular law or to give a specific autonomy to Aceh forever.